ERRORS IN STUDENTS’ WRITING OF PROCEDURE TEXT IN EIGHTH GRADE STUDENTS OF SMP NEGERI 1 JORLANGHATARAN - Mariani Simanjuntak and Johannes Jefria Gultom (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2016)
This study aims at analyzing the errors usage on students’ procedure writing. It was conducted by using qualitative descriptive. The subject of this research was eighth (VIII) grade students of SMP Negeri 1 Jorlanghataran. The number of subjects was taken from two classes. It is VIII-8 and VIII-9 which consist of 60 students. The instrument for collecting data was writing procedure text. The result of the study showed that there are so many errors found on students’ procedure writing. The analysis showed that the most common type of errors made by the students is omission (45,2%). From the data analysis was found that the main causes of errors is Intralingual transfer (59,6%).